Experimental and Computational Study on the Anti‐Markovnikov Hydrofunctionalization of Olefins Using Glycine‐Extended AQ‐Auxiliaries. Issue 11 (21st January 2021) - Nnamdi, Fred U.; Diner, Colin; Champagne, Pier Alexandre; Organ, Michael G.
Abstract: Two similar tridentate directing groups derived from glycine and 8‐aminoquinoline were shown to enable the palladium‐catalyzed anti‐Markovnikov hydrofunctionalization of 4‐pentenylamine with drastically different efficiencies. A computational investigation into the origin of the reactivity difference between these isomeric, carbonyl‐transposed auxiliaries suggests that protonation state, thus charge of the substrate‐metal complex prior to nucleopalladation is key. These investigations have culminated in a directing group design that can undergo Pd‐catalyzed hydrofunctionalization under relatively mild conditions, as low as room temperature. Abstract : Understanding the hydrofunctionalization : A tridentate ligand bearing a quinoline, aryl amide and alkyl amine moieties is highly‐reactive for the anti‐Markovnikov hydrofunctionalization of tethered unactivated olefins, allowing reactions at temperatures as low as 25 °C, while its regioisomer with the amide carbonyl transposed only one position away shows limited reactivity. This experimental and computational study explores the scope of this reaction and demonstrates how the Pd‐substrate complexes employ various favorable or unfavorable protonation states during the mechanism.